The promise of wilderness American environmental politics since 1964 - Turner, James Morton, 1973-; ProQuest (Firm) (Seattle, Wash : University of Washington, 2012)
"From Denali's majestic slopes to the Great Swamp of central New Jersey, protected wilderness areas make up nearly 20 percent of the parks, forests, wildlife refuges, and other public lands that cover a full fourth of the nation's territory. But wilderness is not only a place. It is also one of the most powerful and troublesome ideas in American environmental thought, representing everything from sublime beauty and patriotic inspiration to a countercultural ideal and an overextension of government authority. The Promise of Wilderness examines how the idea of wilderness has shaped the management of public lands since the passage of the Wilderness Act in 1964. Wilderness preservation has engaged diverse groups of citizens, from hunters and ranchers to wildlife enthusiasts and hikers, as political advocates who have leveraged the resources of local and national groups toward a common goal. Turner demonstrates how these efforts have contributed to major shifts in modern American environmental politics, which have emerged not just in reaction to a new generation of environmental concerns, such as environmental justice and climate change, but also in response to changed debates over old conservation issues, such as public lands management. He also shows how battles over wilderness protection have influenced American politics more broadly, fueling disputes over the proper role of government, individual rights, and the interests of rural communities; giving rise to radical environmentalism; and playing an important role in the resurgence of the conservative movement, especially in the American West. "James Turner's insightful book demonstrates the continued vitality and centrality of wilderness within American environmentalism." -Mark Harvey, author of Wilderness Forever: Howard Zahniser and the Path to the Wilderness Act "A superb study of the implementation of the Wilderness Act, and a springboard for a new period in wilderness thought and advocacy." -Paul Sutter, author of Driven Wild: How the Fight Against Automobiles Launched the Modern Wilderness Movement "The most deeply researched, analytically rigorous, and elegantly written study of American wilderness politics since the 1960s yet produced." -from the Foreword by William Cronon James Morton Turner is assistant professor of environmental studies at Wellesley College"--
pt. 1. Wilderness and the origins of modern environmentalism, 1964-1976 -- pt. 2. The polarization of American environmental politics, 1977-1984 -- pt. 3. Wilderness and a new agenda for the public lands, 1987-2009.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Environmental policy -- United States -- History -- 20th century; Environmental protection -- United States -- History -- 20th century; Wilderness areas -- Law and legislation -- United States -- 20th century; Wilderness areas -- United States -- 20th century; Electronic books